Optimizing the Ability to Recognize Letters of Children Aged 4-5 Years Through Letter Card-Based Learning - Nur'aeni Nur'aeni; Sunardi Sunardi; Ahmad Zaini Mukhlis; Sahal Tamrin Marhidi (ALACRITY : Journal of Education, 2026)
The ability to recognize letters is one of the important aspects in the development of early childhood literacy which is the basis for the ability to read and write at the next level of Education. The results of initial observations at TP Cempaka cikakak show that the ability to recognize letters of children aged 4-5 years is still low because learning uses more conventional methods and has not utilized learning media that are interesting and in accordance with the characteristics of children. This study aims to describe the application of letter card media and analyze the improvement of the ability to recognize letters of children aged 4-5 years through the use of these media. The study used the method of classroom Action Research (PTK) with Kemmis and McTaggart model which was carried out in two cycles, including the stages of planning, implementation of action, observation, and reflection. The study subjects were 13 children aged 4-5 years at TP Cempaka Cikakak. Data collection techniques were conducted through observation, interviews, and documentation, while data analysis used quantitative and qualitative descriptive techniques. The results showed that children's ability to recognize letters increased gradually. The average achievement increased from 26.92% in the pre-action phase to 52.12% in cycle I and reached 80.58% in Cycle II. The improvement was seen in the ability of children to recognize letter symbols, name letters, distinguish letter shapes that are almost the same, and connect letters with the initial sound of words. The results showed that the media letter cards effectively improve the ability to recognize letters of children aged 4-5 years and can be used as an alternative learning media to support the development of early literacy in early childhood education.